2022
DOI: 10.1007/s40737-022-00287-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Barriers to Clozapine Prescribing in Patients with Treatment-Resistant Schizophrenia: A Qualitative Study

Abstract: Treatment-resistance schizophrenia (TRS) is one of the psychiatric challenges. While clozapine is an effective treatment for patients with TRS, there are some barriers to clozapine prescribing in these patients. The study aims to explore the barriers from Iranian psychiatrists’ points of view. The study was conducted by a qualitative approach using content analysis. The Participants included 12 psychiatrists who were selected purposefully. Data were collected using a semi-structured interview from May to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…No other published studies within the identified underprioritized areas were found. Instead, eight additional studies on general clinician perspectives on clozapine treatment [203][204][205][206][207][208][209][210] , three additional studies on clozapinepatients' (and their clinicians') attitudes towards their ongoing treatment 40 211 212 , and three additional studies on case-note derived reasons for clozapine cessation or withholding [213][214][215] appeared, ratifying the repetitive behavior of current research and the importance of disseminating these results in order to direct future research towards more meaningful and less well-described areas.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…No other published studies within the identified underprioritized areas were found. Instead, eight additional studies on general clinician perspectives on clozapine treatment [203][204][205][206][207][208][209][210] , three additional studies on clozapinepatients' (and their clinicians') attitudes towards their ongoing treatment 40 211 212 , and three additional studies on case-note derived reasons for clozapine cessation or withholding [213][214][215] appeared, ratifying the repetitive behavior of current research and the importance of disseminating these results in order to direct future research towards more meaningful and less well-described areas.…”
Section: Summary Of Evidencementioning
confidence: 99%